A novel macrolide, solithromycin suppresses mucin overexpression induced by Pseudomonas aeruginosa LPS in airway epithelial cells. Issue 9 (September 2020) - Kawamoto, Yasuhide; Morinaga, Yoshitomo; Kaku, Norihito; Uno, Naoki; Kosai, Kosuke; Sakamoto, Kei; Hasegawa, Hiroo; Yanagihara, Katunori
Abstract: Some macrolides such as 14- and 15-membered macrolides have immunomodulatory effects such as suppression of mucin overproduction. Because a novel macrolide, solithromycin, was developed, we examined whether it suppresses the overexpression of mucin in vitro. A human airway epithelial cell line NCI–H292 was stimulated by Pseudomonas aeruginosa lipopolysaccharides to induce the overproduction of a major mucin, MUC5AC. Treatment with 10 μg/mL of solithromycin significantly inhibited LPS-induced MUC5AC in both mRNA and protein levels as well as a 15-membered macrolide, azithromycin. These findings support that solithromycin has a potential immunomodulatory effect.